Diseño y Evaluación de tres programas alimenticios en la producción de pollos broiler Cobb 500, en el sitio San Roquito del cantón Balsas - Espinoza Salazar, Edison Danilo (2013)
This research work is performed on-site at San Roquito Balsas Canton province of El Oro 2000 chickens were used genetic line COBB 500 , separated into four treatments of 500 birds , subdivided into four replicates of 125 birds were evaluated supply three programs in the first treatment , the food supply was performed according to conventional management guide cobb 500 chicks , the second treatment was a restriction of 5% in relation to the operation guide , the third treatment had a 10% restriction and fourth treatment was given food ad libitum. The following variables were studied feed intake , weight gain , feed conversion, mortality and profitability. The results show that the higher feed intake was recorded in the treatment two ( 5 % restriction ) with 5745 g on average per animal , the best feed conversion was achieved in one treatment (conventional ) with 1.85, the mortality was higher in the treatment four ( will) with 9.4 %, due to hot weather in the area, the higher returns generated in one treatment (conventional ) with 12.53 %.